Curative effect of the aqueous extract of Macaranga barteri Müll.Arg (Euphorbiaceae) on acetic acid induced chronic ulcers in rats (African Journal of Biomedical Research, 2021)
Macaranga barteri (Euphorbiaceae) is used in Côte d'Ivoire for the treatment of several diseases including gastric ulcer. The present study aims to evaluate the curative potential of an aqueous extract of Macaranga barteri leaves (AEMb) in a model of chronic gastric ulcer induced by acetic acid in rats.Chronic gastric ulcers were induced by applying 0.1 ml of acetic acid (30%) to the anterior surface in the region of small curvature of the stomach of rats. Five days after the application of acetic acid, four groups of rats were treated with distilled water (1ml / 100g b.w.), AEMb (250 and 500 mg / kg b.w.) and sucralfate (50 mg / kg b.w.) for 28 days. Then, six rats from each group were sacrificed respectively on the 7th, 14th 21th, 28th days and two weeks after stopping the treatments. Macroscopic analysis of the stomachs, estimated healing percentage of ulcers and histological sections of the stomach were performed.The results obtained showed a healing percentage of ulcerations of 98.22%, 91.47% and 98.07% respectively with sucralfate and AEMb (250 and 500 mg / kg b.w.) after 28 days of  treatment. Two weeks after stopping the treatments with sucralfate and AEMb, all the ulcerations in rats were healed. Study of histological sections showed marked reepithelialization of stomach layers after 28 days of treatment and complete recovery two weeks after stopping treatments unlike treatments of sham-operated control rats.In conclusion, AEMb accelerated the healing of chronic gastric ulcers induced by acetic acid.